Perceptions and needs of health professionals concerning health information systems - Milioris, Konstantinos; Konstantopoulos, Charalampos; Papageorgiou, Konstantinos (Informatica, 2022)
Background: In recent decades, there has been an increasing interest in patients’ needs and their satisfaction with health systems. Various studies have presented several benefits of information management application in health care. Health information technology can contribute to improving health care services performance, cost savings, and greater engagement of patients in their own health. Therefore, many health care organizations are planning to increase their overall adoption of information technology in their activities. Objectives: The aim of our research is to assess health professionals’ views on the adoption and value of health information systems and to assess their usage. Methods: The research focuses on the use of health information technologies in the National Health System in Greece and was performed using a structured electronic questionnaire answered by 1,216 doctors, nurses, and other health care staff. Results: Among the study sample, 92.11% of the hospitals had installed a Health Information System (HIS). Of the respondents, 86.18% believed that the adoption of HIS was extremely important, and 88.8% reported a high or very high frequency of usage in their workplace. However, in 22.3% of the cases, health professionals highlighted the need for integrated information systems: because there was no connection or information exchange installed within the various (clinical and administrative) information systems, this was considered to be a barrier for the effectiveness and improvement of the health care system. Conclusions: The analysis led to the proposal for an information system based on the needs for information and health professionals’ skills in the field of information and communication technologies.